PRODUCTION OF HYDROLATE IN UZBEKISTAN FROM LOCAL RAW MATERIALS (American Journal of Interdisciplinary Research and Development, 2022)
The article provides for the development of recipes for the production of hydrolates in Uzbekistan using local raw materials